Estrutura, Objecto, Eventos. O "outro" arranha-céus - Gonçalo Reinolds Pombo (2019)
The events orchestrated by the movement of bodies in space are one of the neglected layers of architecture and that often reduces it to a knowledge of form, says Bernard Tschumi. Creative manipulation of programs and the elements that confine space is a hypothesis for the enhancement of wished human interactions. Taking events and spaces as two entities that despite being independent, mutually interact, is the overall question throughout the work: are spaces conditioning human interactions, or the opposite? This dissertation is the answer to an international competition which proposes its participants in giving answers on inventive skyscrapers: the design of concepts, which through high-rises, can answer current issues of society. It is explored in the submitted tower, an approach that reduces built form to its structural function, and allows the community to appropriate space. A second complementary layer that occupies the leftovers of the structural elements is filled with the ''family'' of non-static elements, which were called ''objects''. The interventions that fulfill the constant fluctuations of the domestic needs are the initial hypothesis, and it is believed that it can adapt to unusual and delirious needs. In an early stage of the making of the dissertation, software was used in order to produce renders that can enrich the project, and after, the investigations of two main authors proceeded. Bernard Tschumi looks towards architecture through the lens of three entities: space, event, and movement that together create a given program, and utilizes knowledge from other disciplines such as cinema, psychoanalysis, and philosophy, to support his theory. Rem Koolhaas, in a more self-referenced approach, makes use of buildings, social and urban conditions to analyse the contemporary phenomena of globalization. This dissertation is the mirror of a vision, swings between references and idiosyncrasies, and should be understood as a closing chapter, but also the beginning of a study that will long last.